2017
DOI: 10.1097/lbr.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Radial Probe Ultrasound-Guided Cryobiopsy

Abstract: Fluoroscopy-guided transbronchial forceps biopsy has a low diagnostic yield in patients with radiographic suspicion of interstitial lung disease. Cryobiopsy has a higher diagnostic yield likely due to preserved lung architecture and larger biopsies; however, there is an increased risk of major airway bleeding and pneumothorax. Simultaneous use of endobronchial balloon blocker allows for containment of bleeding after cryobiopsy to the affected lobe. In the current article we describe use of radial ultrasound in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…There are no previous studies which assess CLE as a guidance tool for cryobiopsy and only one report about ultrasound-guided cryobiopsy in ILD. In this case series blood vessels could be identified; however, identification of the pleura and areas with dense fibrosis were not described [16]. …”
Section: Discussionmentioning
confidence: 99%
“…There are no previous studies which assess CLE as a guidance tool for cryobiopsy and only one report about ultrasound-guided cryobiopsy in ILD. In this case series blood vessels could be identified; however, identification of the pleura and areas with dense fibrosis were not described [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Much of the technical evolution of cryobiopsy since its original description has centered on improving safety, particularly in protecting against major airway bleeding. Cryobiopsy is clearly capable of producing massive hemorrhage, as several authors have reported (45,48,64). As such, this procedure should only be performed by operators prepared for and adept at the management of major airway bleeding.…”
Section: Bleeding Preparedness and Managementmentioning
confidence: 99%
“…Post-biopsy bleeding was controlled with a 3-minute inflation of this balloon following each biopsy in 84 of 100 procedures (43). Berim et al, reported on their use of radial endobronchial ultrasound to detect significant vascular structures in prospective biopsy target regions in a limited series of six patients, without any major bleeds in this small cohort (48). Two series have piloted the use of two bronchoscopes to allow more rapid re-entry into the airway after each biopsy in lieu of endobronchial blocker use, with low rate of serious hemorrhage reported (44,46).…”
Section: Bleeding Preparedness and Managementmentioning
confidence: 99%
“…Cryobiopsy safety could be further improved with R-EBUS visualisation and avoidance of major blood vessels 5. This case highlights the rare manifestation of lung adenocarcinoma as multiple Cheerio signs, with an added perspective of its appearance from the viewpoint of R-EBUS.…”
Section: Discussionmentioning
confidence: 87%